Covalent modification of proteins by metabolites of NAD+. - Kun, E (1976)
Covalently bound adducts of ply(L-lysine), bovine serum albumin, lysine rich histone (f1) and deoxyribonucleotidase I (DNase, EC 3.1.4.5) with adenosine diphosphoribose and ribose-5-phosphate were prepared at pH 7.4 and 9.5. Macromolecular adducts of bovine serum albumin and histone (f1) were isolated by gel filtration and electrophoresis. Reduction of products by NaBH4 did not dissociate the ribose-5-phosphate moiety from macromolecules. Specific introduction of 3H into the adducts also indicated Schiff base formation. The reaction of ribose-5-phosphate with epsilon-amino groups of histone (f1) approached 70-90% saturation. Spermine and spermidine also react with adenosine diphosphoribose and ribose-5-phosphate to form 1:1 Schiff bases. It is proposed that high turnover of cellular NAD+ is the source of aldehydic metabolites which may regulate macromolecular metabolism by covalent modification of nuclear proteins, whereas polyamines serve as modulators of this control cycle.